SC11 The cambridge undergraduate simulation programme (CUSP). (17th November 2016) - Campbell, A; Jafferji, D; Gopal, A
Abstract : Background: Simulation training is known to improve both competence and confidence in participating individuals. 1 Despite these benefits the undergraduate experience of clinical simulation is variable; an issue a student-run medical education society identified and decided to tackle. Issues thought to limit access to simulation-based medical education (SBME) were thought to include limited availability of teaching staff and the nomadic nature of hospital placements. The aims of the programme were thus defined as: the provision of wide access to safe, clinically robust SBME though the provision of training in clinical simulation facilitation to senior medical students. Methodology: A student-driven management structure was created, to which consultant supervision was integrated for the purpose of ensuring safe and appropriate practice. The student branch of the Association for Simulated Practice in Healthcare (sASPiH) 2 was invited as a stakeholder to provide input and establish strategic relations. These integrations ensured programme was designed with the following principles in mind: patient 3 and learner safety; 4 reliable access to robust and valuable SBME; professional development of student facilitators. Once the programme was designed, a student faculty was recruited, trained, and then validated by consultant faculty. Once validated, the faculty was supported to independently deliver SBME sessions for peers. Outcome: A pilot project has been successfully instigated, involving the training of an initial student faculty of 15. Of these, one student was successfully validated and has provided consultant-approved SBME sessions to peers. Impact: Though not formally assessed at the time, significant value was attached to the initial training by those involved (qualitative feedback). This included appreciation of the need for such a programme as well as satisfaction with the training provided. The limited number progressing to independent delivery was thought to be predominantly due to the logistics of validation organisation. Proof of concept has, however, been demonstrated.